Reasons for admission and neonatal outcome in the neonatal care unit of a tertiary care hospital in Addis Ababa: a prospective study - Tekleab AM; Amaru GM; Tefera YA (Dove Medical Press, 2016)
Atnafu Mekonnen Tekleab,1 Gesit Metaferia Amaru,1 Yemisrach Abeje Tefera21Department of Pediatrics and Child Health, 2Department of Public Health, St Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia Background: The neonatal mortality rate in Ethiopia remains greater than 35 per 1,000 live births. Hence, identifying the reasons for neonatal admission and mortality in a hospital setting is crucial to improve the quality of existing practices in the hospital. The objective of this study was to describe the reasons for admission and the magnitude of neonatal mortality in the neonatal care unit of St Paul's Hospital Millennium Medical College. Methods and subjects: A prospective cohort study was conducted. A total of 216 neonates who were admitted to the neonatal care unit of St Paul's Hospital Millennium Medical College from March 1, 2015, to May 31, 2015, were included in this study. Data fields, determined prospectively, were collected by monitoring the neonates until discharge or death. The independent variables were demographic, obstetric, and clinical characteristics, while the dependent variable was neonatal mortality. Data were analyzed using simple frequencies, odds ratio, and finally binary logistic regression analysis for mortality outcome. Results: The most common primary diagnoses at admission to the neonatal care unit were prematurity with respiratory problem (36.6%), neonatal sepsis (22.7%), and asphyxia (16.2%). Out of the 216 neonates studied, 50 (23.2%) died. High case fatality was observed among neonates with the diagnosis of prematurity with respiratory problem (40.5%) and asphyxia (40.0%). Under multivariate analysis, diagnosis of asphyxia was an independent predictor of mortality (adjusted odds ratio =5.817; 95% confidence interval: 1.611–20.977), while gestational age above the mean of the study population (36.6 weeks) was protective of mortality (adjusted odds ratio =0.683; 95% confidence interval: 0.588–0.795). Conclusion: Nearly a quarter of admitted neonates died. This study identified asphyxia and prematurity as major causes of admission and mortality. Emphasis has to be given to prevent asphyxia and to improve the survival of preterm babies. Keywords: neonate, admission, death, Ethiopia, neonatal outcome, hospital, Addis Ababa